Podolsky electromagnetism at finite temperature: Implications on the Stefan-Boltzmann law - Bonin, C. A. [UNESP]; Bufalo, R. [UNESP]; Pimentel, B. M. [UNESP]; Zambrano, G. E. R. (Amer Physical Soc, 2010)
In this work we study Podolsky electromagnetism in thermodynamic equilibrium. We show that a Podolsky mass-dependent modification to the Stefan-Boltzmann law is induced and we use experimental data to limit the possible values for this free parameter.